Antibiotic use for community-acquired pneumonia in neonates and children: WHO evidence review. (21st December 2018) - Mathur, Shrey; Fuchs, Aline; Bielicki, Julia; Van Den Anker, Johannes; Sharland, Mike
Abstract: Background Pneumonia is the most common cause of death in children worldwide, accounting for 15% of all deaths of children under 5 years of age. This review summarises the evidence for the empirical antibiotic treatment of community-acquired pneumonia in neonates and children and puts emphasis on publications since the release of the previous WHO Evidence Summary report published in 2014. Methods A systematic search for systematic reviews and meta-analyses of antibiotic therapy for community-acquired pneumonia was conducted between 1 January 2013 and 10 November 2016. Results The optimal dosing recommendation for amoxicillin remains unclear with limited pharmacological and clinical evidence. There is limited evidence from surveillance to indicate whether amoxicillin or broader spectrum antibiotics (e.g. third-generation cephalosporins) are being used most commonly for paediatric CAP in different WHO regions. Data are lacking on clinical efficacy in the context of pneumococcal, staphylococcal and mycoplasma disease and the relative contributions of varying first-line and step-down options to the selection of such resistance. Conclusion Further pragmatic trials are required to optimise management of hospitalised children with severe and very severe pneumonia.